How do you find the derivative of y = secx/(1 + tanx)y=secx1+tanx?
1 Answer
Explanation:
First of all, I'm assuming the function is
f(x) = secx/(1 + tanx)f(x)=secx1+tanx
f(x) = (1/cosx)/(1 + sinx/cosx)f(x)=1cosx1+sinxcosx
f(x) = (1/cosx)/((cosx + sinx)/cosx)f(x)=1cosxcosx+sinxcosx
f(x) = 1/cosx xx cosx/(cosx + sinx)f(x)=1cosx×cosxcosx+sinx
f(x) = 1/(cosx+ sinx)f(x)=1cosx+sinx
f(x) = (cosx + sinx)^-1f(x)=(cosx+sinx)−1
We let
The chain rule states that
dy/dx = -1/u^2 xx -sinx + cosxdydx=−1u2×−sinx+cosx
dy/dx = (sinx - cosx)/(sinx + cosx)^2dydx=sinx−cosx(sinx+cosx)2
Hopefully this helps!